2017
DOI: 10.1021/jacs.7b06514
|View full text |Cite
|
Sign up to set email alerts
|

Single Atomic Iron Catalysts for Oxygen Reduction in Acidic Media: Particle Size Control and Thermal Activation

Abstract: It remains a grand challenge to replace platinum group metal (PGM) catalysts with earth-abundant materials for the oxygen reduction reaction (ORR) in acidic media, which is crucial for large-scale deployment of proton exchange membrane fuel cells (PEMFCs). Here, we report a high-performance atomic Fe catalyst derived from chemically Fe-doped zeolitic imidazolate frameworks (ZIFs) by directly bonding Fe ions to imidazolate ligands within 3D frameworks. Although the ZIF was identified as a promising precursor, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
950
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,290 publications
(1,007 citation statements)
references
References 60 publications
30
950
1
7
Order By: Relevance
“…%), the Fe-N-HPC-A possessed al ower total N content of 3.2 at. [9,33,41] Based on the existence of isolated single Fe atomic sites, as identified by HAADF-STEM image, combined with the different configuration of pyridinic Na nd graphitic N, we do speculate that the pyridinicNoffers coordination sites to Fe atoms to form the Fe-N x moieties for increasing the density of active sites. The subsequent heat-treatment led to the total decomposition of unsta- Chem.E ur.J.…”
Section: Active Site Formationo Ff E-n-hpc-ahe Lectrocatalystmentioning
confidence: 76%
See 2 more Smart Citations
“…%), the Fe-N-HPC-A possessed al ower total N content of 3.2 at. [9,33,41] Based on the existence of isolated single Fe atomic sites, as identified by HAADF-STEM image, combined with the different configuration of pyridinic Na nd graphitic N, we do speculate that the pyridinicNoffers coordination sites to Fe atoms to form the Fe-N x moieties for increasing the density of active sites. The subsequent heat-treatment led to the total decomposition of unsta- Chem.E ur.J.…”
Section: Active Site Formationo Ff E-n-hpc-ahe Lectrocatalystmentioning
confidence: 76%
“…%), N( 1.1 at. [9,33] Electrochemical measurement of ORR activity Further rotating ring-diske lectrode (RRDE) measurements indicated that Fe-N-HPC-AH also possessedahigh transferred electron number (> 3.9, highert han those of Fe-N-HPCa nd Fe-N-HPC-A and similar with the commercial Pt/C) with av ery low percentage (< 5%)o fp eroxide yield (% HO 2 À )i nt he whole measured potentialr ange, suggestingt hat the ORR catalysed by Fe-N-HPC-AH progressedt hrough an almost ideal 4-electron path (Figure 3c). %), but the Fe element was hardly detected (Table S1 and Figure S4 in Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the development of efficient non-noble catalysts for ORR has been the focus of many researchers aroundt he world. [4] Of those strategies been reported, [5] using metal-organic frameworks (MOFs) has been proved as an effectivem ean to immobilize highly dispersing MN x active sites in resulting carbonized materials because of their highly ordered structure and uniformly distributed metal struts. [3] It has been revealed that highly dispersing MN x sites embedded in carbon matrix could render the resulting catalystw ith high catalytic activity that rival conventionalP t-based catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…[11,12,19,72] Die Elektronenpolarisierung an der Dotierungsstelle kçnnte die Elektronenaffinitäts owohl der dotierenden Metallatome als auch der ursprünglichen Nichtmetallatome abstimmen und hierdurch die Reaktionskinetik des Ladungstransfers in Nachbarschaft zur Dotierungsstelle verbessern. [74][75][76] Daher kann man durch Dotierung mit Metallatomen wegen deren unvollständiger Koordination nicht nur die Anzahl der aktiven Zentren erhçhen, sondern auch die benachbarten Nichtmetallatome durch Elektronenpolarisierung aktivieren. [66,73] Währenddessen haben die üblicherweise eingesetzten, Kohlenstoff-basierten Nichtmetall-Trägermaterialien typischerweise große Oberflächen und hervorragende Leitfähigkeiten.…”
Section: Angewandte Chemieunclassified